Tinjauan Historis Mengenai Kepentingan Ekonomi Dalam politik Luar Negeri Amerika Serikat Era Isolasionis - Syahdan, Pusparida (Jurusan Hubungan Internasional UNHAS, 2015)
Abstrac:Â Study of US foreign policy are generally divided into two major periods of the isolationist and internationalist. Isolationist period lasted from independence until the eve of World War II, which is characterized by the attitude of the United States who are not actively involved in the international arena.Â However, in this period also witnessed the expansion of the United States to the Pacific and at the same time economic growth extensively. This paper attempts to explain that the US foreign policy in this period is not entirely closed (isolationist) due to economic growth that required the addition of the international market for domestic products. In addition, in the power struggle going on between the major countries in Europe will be difficult if the United States is fully shut down of international relations.Keywords: Isolasionist, American Foreign Policy, Economic Interest